Thoracic endometriosis syndrome in a 75-year-old woman - Amritpal S. Jagra; Ruhma Ali; Alan Klukowicz; Hari Sharma; Richard Miller (European Journal of Case Reports in Internal Medicine)
Thoracic endometriosis syndrome (TES) is a rare condition where endometrial tissue is found in the pleura, parenchyma, and/or diaphragm. Haemoptysis is a common manifestation of pulmonary endometriosis and can be cyclic, aligning with the menstrual cycle. Patients can present with residual cough once menses have stopped. Other manifestations are recurrent pneumothorax and/or pleural effusions associated with menses. On imaging, pulmonary nodules or implants of endometrial tissue along the diaphragm can be present and be confirmed by biopsy. While most cases of TES occur in menstruating females in their thirties on the right side, our case is unique since we report a postmenopausal female with TES on the left side without the typical clinical manifestations.